Analisis perbandingan rencana strategi Baitul Maal wat Tamwil dalam mencapai penetrasi pasar - Rohim, Muhammad; Damya, Valentyno; Putra, Gilang Cahya (Maliki Interdisciplinary Journal, 2023)
This research aims to compare market penetration planning strategies of several Islamic Cooperatives (BMT) in Indonesia, in which BMT Tumang KCS Sukaharjo, BMT Mitra Umat, and BMT al-Mujahidin through SWOT analysis. Market penetration is a marketing strategy aimed at increasing market share or entering new markets with existing products or services. The goal is to acquire more customers or new market share by offering existing products or services to a larger audience or in a broader market area. This study aims to identify the strategies of each BMT in developing market share. This qualitative research utilizes a literature review approach. Data collection techniques involve previous articles. The benefit of this research is to expand knowledge about market penetration strategies in each BMT. Based on the research conducted, the researcher concludes that each BMT has been effective ways to develop their market share through various strategies. BMT Tumang KCS Sukaharjo focuses on operational management and budgeting strategies to gain trust from MSMEs in financing. BMT al-Mujahidin Cilacap emphasizes leveraging strengths, customer needs, business expansion, and adapting to changes in the business environment. BMT Mitra Umat is more focused on marketing mix aimed at increasing a wider market share. Despite these differences, each BMT in different regions continues to strive for broad development with the primary goal of advancing MSMEs for faster growth.